Reading Comprehension and Metacognitive Strategies in First Year Engineering University Students in Pakistan - Mansoor Ahmed, Channa; Abdul Malik, Abassi; John, Stephen; Jam Khan, Mohammad; Masood, A. Memon; Zaimuariffudin Shukri, Nordin (Canadian Center of Science and Education, 2018)
The paper investigates the use of metacognitive strategies by first year engineering students at the time of classroom practice on reading text. The study was conducted in four engineering departments of a university in Pakistan. Data was collected through focus group interviews of first year engineering students. The researchers developed interview questions which were validated by two experts at university Malaysia Sarawak. Students were divided into 8 groups and each group had 5 informants. The data was recorded in audio-tape and organized gathered data through NVivo version 8 for interpretation of the results. The most important themes were generated through data analysis including thinking through images of the texts, selecting the main ideas, selecting the topic sentences, scanning of the texts, summarizing of the texts, and Questioning. The study contributed theoretically by giving the most promising results which showed that more than half of these groups used metacognitive strategies in classroom reading practice while less than half of groups did not use strategies and remained poor in reading comprehension. This study proposed to develop reading comprehension courses and syllabus based on reading strategies for engineering students.